The Transformation of Neo-Ottomanism Under Justice and Development Party (JDP) Rule in Turkey (2002–2022): The Central Asian Vector - Marmontova, Taissiya; Zhiyenbayev, Miras; Vaseneva, Ekaterina (Vestnik Volgogradskogo gosudarstvennogo universiteta. Serii͡a︡ 4, Istorii͡a, 2023)
Introduction. The paper describes aspects of the transformation of neo-Ottomanism under Justice and Development Party (JDP) rule in Turkey (2002–2022), with a focus on the situation in Central Asia. Methods and materials. The article employs the case study method and examines the Central Asian vector of Turkish foreign policy from 2002 to 2022. Analysis. Since the collapse of the Soviet Union, filling the political power void in Central Asia has been one of Turkey’s key foreign policy interests. This interest was reinvigorated by the domestic political transformation in light of the accession of the Justice and Development Party in 2002. The neo-Ottomanism that formed the basis of JDP’s foreign policy, on the one hand, elaborated on the Ottomanism of the last century and, on the other hand, mirrored the changes in the political system of the country after 2013, such as the authoritarianization of the ruling regime and the rise of Islam as a tool for public support consolidation. Results. As a result, the conclusion was drawn that over the past twenty years, neo-Ottomanism has come to represent a broadly circumscribed liberal economic approach combined with an appeal not only to the common Ottoman past and pan-Turkic sentiments but also to the Muslim present. Meanwhile, Turkey’s cultural and religious rapprochement with the region is driven by its strategic economic interests, for which Central Asia is an integral component of Turkey’s new international role. Thus, Turkey’s policy towards Central Asian states reverberates the outcome of the transformation of the neo-Ottoman discourse as a product of the country’s changing domestic political landscape while shedding light on the strategic priorities it encompasses: becoming a regional hub and a proactive regional power. Authors’ contributions. T.V. Marmontova – preparation of the structure of the article, methodology, and review of literature, M.B. Zhiyenbayev – “Regionalization” of foreign policy of Turkey and the place of Central Asia in the pan-Turkic picture of the world, E.A. Vaseneva – assessment of the policy of the Justice and Development Party in Turkey in 2002–2022.